PREVALÊNCIA DE LESÕES OSTEOMUSCULARES EM JOGADORES DE FUTEBOL ACREANOS NAS TEMPORADAS 2016-2018 - Jader de Andrade Bezerra; Aristéia Nunes Sampaio; Jeane Maria Moura Costa; Jaqueline dos Santos Valente Barros; Jefferson Teixeira Sarmento de Lima; Antonio Clodoaldo Melo de Castro (Journal of Physical Education)
ABSTRACT The aim of the present study was to assess the prevalence of musculoskeletal injuries in professional soccer players in the state of Acre, Brazil, during the 2016, 2017 and 2018 seasons. Method: The sample consisted of 112 professional soccer players. Data were collected from the medical records of injured players and through interviews (players and/or those responsible for their treatment). The following data on the characteristics of the injuries were collected: injury type, whether the injury occurred during matches or training, injured site, and player position. Results: stretch 38 (33,9%) and contractures 41 (36,6%) were the most common injury types, followed by contusions 9 (8,0%), dislocations 6 (5,4%) and tendonitis 5 (4,5%) . The lower limbs were the most affected, with the back of the thigh, knee and ankle being the sites with the highest injury frequencies. Winger and midfielder were the positions with the highest prevalence of injuries. In 2016, the prevalence of injuries was higher during matches than training, and in the subsequent seasons, there was a higher prevalence during training. Conclusion: The prevalence of injuries in soccer players from Acre is high and mainly involves the lower limbs, with a higher frequency among wingers, attacking midfielders and strikers. Methods for preventing such injuries are necessary.